PENGARUH MOTIVASI DAN KREATIVITAS TERHADAP MINAT BERWIRAUSAHA MAHASISWA PRODI PENDIDIKAN EKONOMI DI FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS NIAS RAYA - Serli Zana Gulo (Jurnal Ilmiah Mahasiswa Nias Selatan, 2026)
This research aims to determine the influence of motivation and creativity on the entrepreneurial interest of Economic Education Students at the Faculty of Teacher Training and Education, Nias Raya University. The type of research used in this research is quantitative research with a causal nature. The population in this study was 265 Economic Education Study Program students at the Faculty of Teacher Training and Education, Nias Raya University. The sampling technique uses a stratified sampling technique, with a sample size of 73 people. The data collection technique used in this research is the questionnaire technique. The analytical method that will be used to test the hypothesis used in this research is multiple linear regression analysis. The results of this research show that motivation and creativity have a positive and significant effect on interest in entrepreneurship. The conclusion of this research is that, partially, the motivation variable influences the interest in entrepreneurship of students in the Economic Education study program at Nias Raya University and the creativity variable influences the interest in entrepreneurship of students in the Economic Education study program at Nias Raya University, and simultaneously the motivation variable and the creativity variable influence the interest in entrepreneurship of students in the Education study program. Nias Raya University of Economics. The suggestion in this research is that to increase interest in entrepreneurship, students should first choose motivation both internally and externally and have creativity in entrepreneurship. With the motivation and creativity possessed by students, it will increase interest in entrepreneurship.